2002
DOI: 10.1080/07388550290789522
|View full text |Cite
|
Sign up to set email alerts
|

Promiscuity of Hosting Nitrogen Fixation in Rice: An Overview from the Legume Perspective

Abstract: The subject area of this review provides extraordinary challenges and opportunities. The challenges relate to the fact that the integration of various fields such as microbiology, biochemistry, plant physiology, eukaryotic as well as bacterial genetics, and applied plant sciences are required to assess the disposition of rice, an alien host, for establishing such a unique phenomenon as biological nitrogen fixation. The opportunities signify that, if successful, the breakthrough will have a significant impact o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2004
2004
2008
2008

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 234 publications
(204 reference statements)
0
3
0
Order By: Relevance
“…In this symbiotic organ, the bacteria, differentiated into bacteroids, fix nitrogen for the plant host (Schultze and Kondorosi 1998, Galvez et al 2000). There has been much interest in exploring the feasibility of transferring symbiotic nitrogen fixation capability to important cereals such as rice (reviewed by Dey and Datta 2002), considering the need for a continuous efficient supply of nitrogen for enhanced rice yield. Taking a methodical stepwise approach might be interesting to analyse the ability of rice roots, an alien host, to create an appropriate physiological environment to host rhizobia akin to fix nitrogen in legumes.…”
Section: Introductionmentioning
confidence: 99%
“…In this symbiotic organ, the bacteria, differentiated into bacteroids, fix nitrogen for the plant host (Schultze and Kondorosi 1998, Galvez et al 2000). There has been much interest in exploring the feasibility of transferring symbiotic nitrogen fixation capability to important cereals such as rice (reviewed by Dey and Datta 2002), considering the need for a continuous efficient supply of nitrogen for enhanced rice yield. Taking a methodical stepwise approach might be interesting to analyse the ability of rice roots, an alien host, to create an appropriate physiological environment to host rhizobia akin to fix nitrogen in legumes.…”
Section: Introductionmentioning
confidence: 99%
“…Kouchi et al [10] showed that the rice Osenod40 gene had a similar expression pattern compared to that from soybean Gmenod40. Dey et al [7,11] indicated that the expression of Medicago truncatula enod40 in both Medicago truncatula and transgenic rice appeared in a similar way: an enod40-mediated root growth response was inhibited by ethylene in both plants.…”
mentioning
confidence: 97%
“…Because of its small genome and amenability to transformation, we chose rice as a model plant to work with. In addition, since rice is an important staple crop, studying its potential for nitrogen fixation is of significance for economic development [7] . Ultimately, the ability of rice to respond to Nod-factor signals depends on its genetic predisposition to acquire the ability to nodulate and fix nitrogen.…”
mentioning
confidence: 99%